Contexts of Silence and Disclosure in Women’s Experiences of Workplace Harassment - Yang, Yaliu (Psychology of Woman Journal, 2025)
Objective: This study aimed to explore how women in Chile experience, interpret, and navigate silence and disclosure in the context of workplace harassment. Methods and Materials: Using a qualitative, interpretive design, the study employed semi-structured in-depth interviews with 17 women from diverse professional sectors in Chile, including education, healthcare, public administration, and corporate organizations. Participants were selected through purposive sampling, and data collection continued until theoretical saturation was achieved. Interviews were conducted in Spanish, transcribed verbatim, and analyzed using thematic analysis in NVivo 14 software following Braun and Clarke’s (2006) framework. The analysis identified recurrent patterns and contextual dynamics shaping participants’ decisions to remain silent or disclose their experiences. Ethical approval was secured to ensure confidentiality, informed consent, and voluntary participation. Findings: The analysis generated four major themes: (1) Culture of Silence and Fear, reflecting institutional tolerance, power asymmetry, and fear of retaliation; (2) Psychological and Social Consequences, encompassing emotional exhaustion, identity disruption, and withdrawal; (3) Pathways to Disclosure, illustrating incremental, strategic, and collective disclosure processes; and (4) Healing and Resistance, describing women’s efforts to reclaim agency through storytelling, solidarity, and advocacy. Findings revealed that silence was a learned survival strategy shaped by structural inequities, while disclosure emerged as a negotiated act dependent on social support, trust, and contextual safety. Conclusion: The study highlights that workplace harassment is sustained by systemic silence rooted in fear, gender hierarchy, and institutional neglect. However, women’s acts of disclosure and resistance signify transformative pathways toward empowerment and organizational change.